Physical Literacy and Practicum Experience as Predictors of Inclusive Physical Education Self-Efficacy - M. Asri B (International Journal of Humanities, Education, and Social Sciences, 2026)
Inclusive physical education requires pre-service primary teachers to adapt instructional tasks, communicate learning expectations, ensure safety, and sustain meaningful participation among learners with diverse abilities. This study aims to examine whether physical literacy and practicum experience predict inclusive physical education teaching self-efficacy among pre-service primary teachers at Universitas Negeri Makassar, Indonesia. The proposed study employs a cross-sectional explanatory design involving approximately 160–220 students in the Primary School Teacher Education program who have completed foundational physical education coursework. Physical literacy will be measured using an adapted instrument for university students, while inclusive teaching self-efficacy will be assessed across six dimensions: planning, instructional adaptation, communication, assessment, safety, and collaboration. Practicum experience will be operationalized according to verified practicum hours and the quality of interactions with learners in school settings. Hierarchical regression analysis will estimate the unique contributions of physical literacy and practicum experience after controlling for semester, prior disability-related coursework, and personal physical activity. As data collection has not yet been completed, the draft does not report empirical findings; any numerical results incorporated for structural demonstration are simulated and must be replaced with field data before submission. Conceptually, the study positions inclusive teaching self-efficacy as an outcome of both embodied competence and authentic teaching exposure. Its findings are expected to inform the design of primary teacher education programs that prepare generalist teachers to deliver safe, adaptive, and participatory physical education in increasingly diverse classrooms.